2020
DOI: 10.1038/s41467-020-15484-6
|View full text |Cite
|
Sign up to set email alerts
|

Irreversible accumulated SERS behavior of the molecule-linked silver and silver-doped titanium dioxide hybrid system

Abstract: In recent years, surface-enhanced Raman scattering (SERS) of a molecule/metal-semiconductor hybrid system has attracted considerable interest and regarded as the synergetic contribution of the electromagnetic and chemical enhancements from the incorporation of noble metal into semiconductor nanomaterials. However, the underlying mechanism is still to be revealed in detail. Herein, we report an irreversible accumulated SERS behavior induced by near-infrared (NIR) light irradiating on a 4-mercaptobenzoic acid li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
76
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 124 publications
(82 citation statements)
references
References 65 publications
1
76
0
Order By: Relevance
“… 104 (Copyright 2019, John Wiley & Sons, Inc.) (C), and Zhou et al. 107 (Copyright 2020, Nature Publishing Group) (D). …”
Section: Main Textmentioning
confidence: 99%
“… 104 (Copyright 2019, John Wiley & Sons, Inc.) (C), and Zhou et al. 107 (Copyright 2020, Nature Publishing Group) (D). …”
Section: Main Textmentioning
confidence: 99%
“…It is found that the Raman shift intensity of our proposed flexible SERS substrate tends to increase with the decrease of the temperature. Slight increase in the intensity of Raman scattering is observed from the counterpart of Au/Si ribbon due to the temperature effect on Raman scattering of RhB, [ 57 ] as shown in Figure S10, Supporting Information. Detailed Raman spectra measured at different temperatures are shown in Figure S11, Supporting Information.…”
Section: Resultsmentioning
confidence: 99%
“…The results show that Nd doping can narrow the bandgap of TiO 2 , but the bandgap shows less change with the increase in doping concentration. Nd doping can improve the optical absorption property and SERS performance of TiO 2 NPs substrates, which is attributed to morphology, defects, and incorporation of impurities during synthesis in nanomaterials [ 29 , 32 , 45 ].…”
Section: Resultsmentioning
confidence: 99%
“…Among them, ion doping is a highly effective method, increasing the defect concentration and adjusting the bandgap of SERS substrates. Zhou et al [ 29 ] reported a substantial enhancement of the SERS signal by near-infrared (NIR) light illumination with a hybrid system consisting of silver and silver-doped titanium dioxide and adsorbed 4-MBA (4-MBA/Ag/Ag-doped TiO 2 ), which was attributed to the higher crystallinity of the substrate and the promoted CT. Tian et al [ 30 ] used 2D SnSe 2 nanosheets as SERS substrates, which essentially broke the limitations of 2D semiconductors for SERS applications and obtained a Raman signal intensity of R6G that was 1.3 to 1.7 times higher than that of pure SnSe 2 . Yang et al [ 31 ] developed a novel sensitive Mo-doped Ta 2 O 5 semiconductor substrate by the “coupled resonance” effect, which can detect methyl violet (MV) molecules up to 9 × 10 −9 M. This SERS enhancement effect can be attributed to (i) MV molecular resonance, (ii) CT resonance between MV and Ta 2 O 5 , and (iii) electromagnetic enhancement around the gap and tip of the substrate.…”
Section: Introductionmentioning
confidence: 99%